Pentahelix model in agrotourism area development in Karo Regency - Helena Tatcher Pakpahan; Siti Normi Sinurat; Donny Simatupang (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This research aims to expand the triple helix strategy by involving various elements of society and non-profit institutions in order to realize innovation in the Development of Agrotourism Areas in Karo Regency.The Penta helix model in the development of agrotourism in Karo Regency are academics, society, government, media and business. The method of determining the sample was determined purposively (deliberately) in the agrotourism area in Karo Regency, North Sumatera Province. This sampling method using purposive sampling is a technique that is not based on random, regional or start but based on considerations that focus on certain goals. This study uses a qualitative approach, which means that research with its findings is not obtained from statistical procedures or forms of calculation that emphasize the essence of the phenomenon under study. The result of this study indicate that there are five institutions that play a role in the development of agrotourism in Karo Regency, namely: (1) Academics are University North Sumatera (USU), Indonesian Methodist University (UMI), Medan Area University (UMA), UMSU; (2) The community is a tourism-aware group; (3) The government is the village government, the agriculture office the tourism office; (4) Media, namely print media and online media; and (5) Banking (BRI, BNI).